Effects of data-driven feedback on nurses' and physicians' hand hygiene in hospitals - a non-resource-intensive intervention in real-life clinical practice - Anne-Mette Iversen; Marco Bo Hansen; Svend Ellermann-Eriksen (Elsevier, 2023)
Summary: Background: Hand hygiene (HH) by healthcare workers (HCWs) is one of the most important measures to prevent hospital-acquired infections. However, HCWs struggle to adhere to HH guidelines. We aimed to investigate the effect of a non-resource intensive intervention with group and individual feedback on HCWs HH in a real-life clinical practice during the COVID-19 pandemic. Methods: In 2021, an 11-month prospective, interventional study was conducted in two inpatient departments at a Danish university hospital. An automated hand hygiene monitoring system (Sani Nudge™) was used to collect data. HH opportunities and alcohol-based hand rub events were measured. Data were provided as HH compliance (HHC) rates. We compared HHC across 1) a baseline period, 2) an intervention period with weekly feedback in groups, followed by 3) an intervention period with weekly individual feedback on emails, and 4) a follow-up period. Results: We analyzed data from physicians (N=65) and nurses (N=109). In total, 231,022 hygiene opportunities were analyzed. Overall, we observed no significant effect of feedback, regardless of whether it was provided to the group or individuals. We found a trend toward a higher HHC in staff restrooms than in medication rooms and patient rooms. The lowest HHC was found in patient rooms. Conclusions: The automated hand hygiene monitoring system enabled assessment of the interventions. We found no significant effect of group or individual feedback at the two departments. However, other factors may have influenced the results during the pandemic, such as time constraints, workplace culture, and the degree of leadership support.